The Analysis of the Effect of BI Rate, Purchasing Power Index, Domestic Investment, and Labor Force Participation Rate on per Capita Expenditure in East Java Province - Susanto, Doni Tri; Imaningsih, Niniek (Journal of Regional Economics and Development, 2025)
This study aims to analyze the partial and simultaneous effects of BI Rate, Purchasing Power Index (IDB), Domestic Investment (PMDN), and Labor Force Participation Rate (LFPR) on Per Capita Expenditure in East Java Province. This study uses annual time series data for the period 2009–2013 sourced from the Central Statistics Agency (BPS) and Bank Indonesia (BI). The analytical method used is multiple linear regression with EViews 13 software. The results of the classical assumption test show that the model meets the requirements of normality, and there is no multicollinearity, heteroscedasticity, and autocorrelation. The results reveal that partially, BI Rate and the Purchasing Power Index have a positive and significant effect on per capita expenditure. Meanwhile, Domestic Investment (PMDN) and Labor Force Participation Rate (LFPR) did not show a significant effect. However, simultaneously, the four independent variables proved to have a significant effect on per capita expenditure. These findings provide policy implications that efforts to improve the welfare of the people of East Java must consider a combination of prudent monetary policy, programs to increase purchasing power, as well as more targeted and inclusive investment and employment strategies.